In vitro elution and dissolution of tobramycin and gentamicin from calcium phosphate - Che Seman, Che Nor Zarida; Othman, Fauziah; Abdul Kadir, Arifah; Ahmad, Azfar Rizal; Mohd Yusof, Nazri; Zulkifly, Ahmad Hafiz; Mustaffa, Rusnah; Goriman Khan, Mohd Azam Khan; Saidi, Hasni Idayu (Academic Journals, 2011)
This study was conducted to investigate the in vitro drug release characteristics of tobramycin and gentamicin from calcium phosphate. Calcium phosphate beads were loaded with tobramycin and gentamicin separately to form 2 types of antibiotic beads to generate antibiotic drug delivery system for the treatment of osteomyelitis. Tobramycin and gentamicin concentrations were determined spectrophotometrically by measuring the absorbance at 400 nm. The standard graphs for tobramycin and gentamicin concentration versus absorbance reading were prepared as references to identify the concentration of the drugs release after incorporating calcium phosphate over 8 weeks. This study showed that incorporating tobramycin and gentamicin with calcium phosphate provided slow residual release of antibiotic from 30 min to 1344 h (8 weeks) and dissolution of calcium phosphate. In this respect, the drug delivery systems of tobramycin and gentamicin-incorporated calcium phosphate have potential of controlling drug release.